The crisis imperative : crisis rhetoric and welfare state reform in Belgium and the Netherlands in the early 1990s - Kuipers, Sanneke (Changing welfare states., 2006)
Discusses two distinct approaches to welfare state reform in two European Union countries faced with mounting costs of 'welfare without work'